Artificial Intelligence: The Future in Dentistry - Smita R. Priyadarshini1, Pradyumna Ku Sahoo2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Artificial intelligence (AI) is an area of computer technologies in influencing our lives. These functions bydigital use of algorithms to learn data and form statistical patterns to understand the outcomes thus help indecision making. This article reviews the utility of AI in health care in precise diagnosis and better treatmentand patient care. It would provide superior quality and comprehensive patient care in dentistry. Theseinnovations would enable dentists to work with precision in all aspects of diagnosis and treatment planning.